46.0k views
1 vote
Factor completely 4x^2-8x-60​

User Bram Z
by
6.0k points

2 Answers

4 votes

Answer:

4(x - 5)(x + 3)

Explanation:

Given

4x² - 8x - 60 ← factor out 4 from each term

= 4(x² - 2x - 15)

To factor the quadratic

Consider the factors of the constant term ( - 15) which sum to give the coefficient of the x- term ( - 2)

The factors are - 5 and + 3, since

- 5 × 3 = - 15 and - 5 + 3 = - 2, hence

x² - 2x - 15 = (x - 5)(x + 3) and

4x² - 8x - 60 = 4(x - 5)(x + 3)

User Metasequoia
by
5.7k points
3 votes
The answer is (4)(x-5)(x+3)
Factor completely 4x^2-8x-60​-example-1
User Amit Soni
by
5.1k points